Dissociative electron attachment to molecular chlorine. (August 2015) - Gope, Krishnendu; Prabhudesai, Vaibhav S; Mason, Nigel; Krishnakumar, E
Synopsis: We report the study of dissociative electron attachment to molecular chlorine in the energy range of 1 to 20 eV using velocity slice imaging technique. Based on the angular distributions at various electron energies, we identify the partial waves involved in the resonance formation that lead to DEA.